(untitled) - Allen, John L. (Guilford, CT., 2004)
The Student Atlas of Anthropology contains 118 full-color maps. Prepared jointly by professors of geography and anthropology, the collection is both unique and comprehensive in its scope. It displays the human past and its evolution to the present day in relationship to the physical world. In the maps on these pages, students can go beyond their textbooks and actually see the interplay of physical geographical features/environmental patterns and human biological, archaeological, linguistic, and cultural development.
Keywords: Anthropology,Ethnology,Archaeology,Human geography,Atlases,Nhân loại học,Nhân chủng học,Khảo cổ học,Địa lý con người,Tập bản đồ